2013
DOI: 10.1007/s11060-013-1065-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for recurrent epidermoid cyst

Abstract: Intracranial epidermoid cysts are rare benign congenital lesions for which the mainstay of treatment has been surgical resection. Due to a propensity to grow along the skull base, subtotal resection is often elected to avoid excessive surgical morbidity, but it comes with an increased risk of recurrence with its associated treatment difficulties. We here present the cases of three patients with recurrent epidermoid cyst who underwent multiple surgical resections followed by external beam radiation therapy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For patients who have failed surgical treatment or recurrence is documented, radiotherapy has been used as an alternative with fairly good results. The effects of radiotherapy on ET have been assessed in a few case reports,[ 5 7 12 ] and tumor control, as the main goal, can be achieved by this method, with relatively low complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who have failed surgical treatment or recurrence is documented, radiotherapy has been used as an alternative with fairly good results. The effects of radiotherapy on ET have been assessed in a few case reports,[ 5 7 12 ] and tumor control, as the main goal, can be achieved by this method, with relatively low complications.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has not been used extensively to treat ET, but several reports of its efficacy have been published. [ 5 7 12 ] Even fewer cases treated with radiosurgery have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, craniopharyngiomas most commonly stem from the infundibulum and are composed of squamous epithelium; however, nearly 60% of these tumors have calcification present [ 5 , 15 ]. In contrast, epidermoid cysts are filled with keratin debris, lipid, and water and appear hypodense on CT [ 6 , 15 ]. While our patient’s neoplasm had a detached fragment that was calcified, these tumors are often present in the pediatric population and present with endocrine symptoms in addition to vision loss [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it is still unclear if the degree of resection is predictive of recurrence, it has been suggested that it is most likely the re-accumulation of cyst contents that causes the appearance of symptoms [ 6 ]. As of 2003, the recurrence rate for intracranial epidermoid cysts was stated at 24% [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Some studies have indicated radiotherapy as an alternative to the failure in surgical treatment or recurrence, and tumor control can be achieved through this method. 16…”
Section: Discussionmentioning
confidence: 99%